Pengaruh Senam Hamil terhadap Penurunan Ketidaknyamanan Nyeri Punggung dan Nyeri Pinggang pada Ibu Hamil Trimester III - Hastuti Usman; Siti Hadijah Batjo; Fitriani Dalle; Lili Suryani (Jurnal Bidan Cerdas, 2021)
Introduction: Back pain and low back pain are discomforts that are often encountered in third trimester pregnant women this is due to changes in the structure of the mother's body due to increasing gestational age. Purpose: The purpose of this research was to determine the effect of pregnancy exercise on reducing the discomfort of back pain and low back pain in third trimester pregnant women. Methods: This research was a pre-experimental research design with the One Group Pre test - Post test Design approach. The sample of this research was third trimester pregnant women who experienced back pain and low back pain in the Mamboro Public Health Center area. The number of samples of this research was 33 people, taken using total sampling technique. The hypothesis of this research is accepted that there is an effect of pregnancy exercise on reducing the discomfort of back pain and low back pain in third trimester pregnant women in the Mamboro Public Health Center area in Palu. Results: The analysis used univariate and bivariate analysis using the Wilcoxon test. Based on the results of the bivariate analysis using the Wilcoxon test analysis, it indicates that the ρ value of back pain before and after pregnancy exercise is 0.002 (<0.05) and the ρ value of low back pain before and after pregnancy exercise is 0.029 (<0.05). Conclusion: Thus, there is an effect of pregnancy exercise on reducing the discomfort of back pain and low back pain in third trimester pregnant women.